The Use Of Digital Marketing In Hydroponic Marketing (Case Study Of Cv. Family Garden Mart In Baruga District, Kendari City) - M., Kesia; Saediman; Yusria, Wa Ode (International journal of technology and education research, 2026)
This study aims to: (1) identify the types of digital marketing platforms used by CV. Family Garden Mart and their contribution to marketing activities, (2) analyze the contribution of digital marketing to sales volume and marketing performance compared to conventional marketing methods, and (3) examine the digital marketing strategies applied in promoting hydroponic vegetables. This research employs a descriptive method with a qualitative and simple quantitative approach through a case study. Data were collected through interviews, observations, and documentation. The results indicate that CV. Family Garden Mart utilizes several digital marketing platforms, including WhatsApp, Facebook, Instagram, and TikTok. Among these, WhatsApp is the most frequently used platform for direct communication and transactions with consumers, while Instagram and TikTok serve as effective tools for enhancing product visibility and consumer awareness. The implementation of digital marketing has made a significant contribution to increasing the sales volume of all types of hydroponic vegetables compared to conventional marketing approaches. The applied digital marketing strategies include visual content marketing, interactive communication with consumers, and the utilization of social media as a medium for product promotion and education